Building information modelling strategies in sustainable housing construction projects in Malaysia - Rahim, Nur Syafika Artika; Ismail, Syuhaida; Subramaniam, Chitdrakantan; Abdullah Habib, Siti Nora Haryati; Durdyev, Serdar (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Building Information Modelling (BIM) plays a very significant role in the construction industry, especially in project management decision-making and data integration efforts during the preliminary planning and design stage. This is aligned with the National Construction Policy (NCP 2030) by the Ministry of Work Malaysia, highlighting that it is timely for the construction industry players to move towards sustainability. BIM must be implemented to ensure the smooth delivery of sustainable housing construction projects in Malaysia due to its critical role in assisting in construction cost optimisation, green building implementation, minimising environmental impact, and waste reduction. However, the BIM implementation rate in Malaysia is still minimal due to the challenges in its execution. Therefore, this paper is aimed to propose BIM’s critical strategies in the development of Malaysian sustainable housing construction projects as envisaged in the United Nations Sustainable Development Goals (UNSDGs). A thorough systematic literature review and questionnaire survey of fifty (50) BIM players in housing construction projects in Malaysia shows that from sixteen (16) BIM strategies, three (3) items are identified as critically important strategies, whereas another five (5) items are identified as important strategies. The outcome of the study shall benefit the construction industry players who are involved in the sustainable housing construction project and mainly drives the PublicWork Department (PWD) BIM Strategic Plan 2021–2025, thus supporting the earlier mentioned NCP 2030 agenda by the Ministry ofWork Malaysia.